Упрости выражение (а+2)(а-3)-(а-2)² если а=2/7​


Упрости выражение (а+2)(а-3)-(а-2)² если а=2/7​

Sadist702 Sadist702    2   08.11.2020 22:59    0

Ответы
eviljew1 eviljew1  08.12.2020 23:00

-9 1/7

Пошаговое объяснение:

(а+2(а-3)-(а-2)²=а²-3а+2а-6-(а²-4а+4)=а²-а-6-а²+4а-4=3а-10

Если а=2/7, то 3а-10=3*2/7-10=6/7-10=6/7-9 7/7=

-9 1/7

ПОКАЗАТЬ ОТВЕТЫ
nikadey1 nikadey1  08.12.2020 23:00

а^2-3а+2а-6-а^2+4а-4=

3а-10;

а=7/9

3×7/9-10=7/3-10=2 1/3-10= -7 2/3

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика